2011
DOI: 10.1007/s11069-011-9818-4
|View full text |Cite
|
Sign up to set email alerts
|

Landslide influence on turbidity and total solids in Cubatão do Norte River, Santa Catarina, Brazil

Abstract: The rainfall events that occurred in the Cubatão do Norte River watershed, Santa Catarina State, Brazil, in 2008, were characterized by both high intensities and amounts and triggered landslides in this watershed. The objective of the present study was to analyze the influence of landslides on the turbidity and the total solid concentration (TS) in this river using turbidity, TS, and river discharge data obtained from March 23, 2008, to June 11, 2010. The comparison between turbidity and discharge patterns imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 9 publications
(9 reference statements)
0
4
0
4
Order By: Relevance
“…In other words, landslide occurrences significantly increase the quantity of sediments in the rivers. Analyzing the landslide influence on discharge and turbidity in a river in the municipality of Joinville, Santa Catarina State, Brazil, Kobiyama et al (2011) reported that the landslide occurrence damaged the city´s water supply operation system. This type of water supply problem would be very common in the town of Alfred Wagner because the Caeté river provides for its principal water resources.…”
Section: Resultsmentioning
confidence: 99%
“…In other words, landslide occurrences significantly increase the quantity of sediments in the rivers. Analyzing the landslide influence on discharge and turbidity in a river in the municipality of Joinville, Santa Catarina State, Brazil, Kobiyama et al (2011) reported that the landslide occurrence damaged the city´s water supply operation system. This type of water supply problem would be very common in the town of Alfred Wagner because the Caeté river provides for its principal water resources.…”
Section: Resultsmentioning
confidence: 99%
“…As inundações são importantes processos fluviais, formadores de feições como a planície de inundação, terraços e diques marginais, além de contribuir para a manutenção do ecossistema fluvial (CHRISTOFOLETTI, 1980;1981). Os escorregamentos são processos modeladores da paisagem responsável pela oferta de sedimentos (KOBIYAMA et al, 2011), pela manutenção de canais de primeira ordem (DIETRICH et al, 1986), pelo recuo das vertentes e modificação da forma da encosta. Terremotos e vulcanismo são responsáveis pela criação, destruição e deslocamento de ilhas, por desencadearem escorregamentos, tsunamis, entre outros processos modificadores da paisagem.…”
Section: Desastres Naturais Conceitosunclassified
“…A variabilidade climática e os seus impactos sempre estiveram presentes na história da humanidade e nos últimos anos vêm deixando o mundo em alerta e desafiando os pesquisadores a desvendar as rápidas e severas mudanças do clima no mundo (KOBIYAMA et al, 2011). Uma discussão quase que unânime é que a intensidade desses eventos serão potencializadas.…”
Section: Introductionunclassified